A functional role for NS5ATP9 in the induction of HCV NS5A‐mediated autophagy. Issue 6 (20th August 2013) - Quan, M.; Liu, S.; Li, G.; Wang, Q.; Zhang, J.; Zhang, M.; Li, M.; Gao, P.; Feng, S.; Cheng, J.
Summary Autophagy has been shown to facilitate replication of hepatitis C virus (HCV); however, the mechanism by which HCV induces autophagy has not been fully established. NS5A, a nonstructural protein expressed by HCV, regulates numerous cellular pathways, including autophagy, by up‐regulating Beclin 1; however, the underlying mechanism remains unclear. To obtain new insights into HCV‐regulated autophagy, NS5ATP9 was overexpressed in HepG2 and L02 cells, resulting in up‐regulation of endogenous Beclin 1 mRNA and protein levels, respectively. The luciferase‐reporter assay results showed that both NS5A and NS5ATP9 could transactivate Beclin 1 promoter activity, but that NS5A could not transactivate the Beclin 1 promoter in NS5ATP9‐silenced HepG2 and L02 cells. Up‐regulation of Beclin 1 mRNA and protein expression by NS5A could also be attenuated by NS5ATP9 knock‐down. Furthermore, the HepG2 and L02 cells that transiently overexpressed NS5ATP9 had enhanced accumulation of vacuoles carrying the autophagy marker LC3, consistent with the conversion of endogenous LC3‐I to LC3‐II. In contrast, the conversion of endogenous LC3‐I to LC3‐II could not be enhanced by NS5A in NS5ATP9‐silenced HepG2 cells. These results highlight an important potential role for NS5ATP9 in HCV NS5A‐induced hepatocyte autophagy.